Cover Picture: The Sound of Batteries: An Operando Acoustic Emission Study of the LiNiO2 Cathode in Li–Ion Cells (Batteries & Supercaps 10/2020). Issue 10 (16th September 2020) - Schweidler, Simon; Bianchini, Matteo; Hartmann, Pascal; Brezesinski, Torsten; Janek, Jürgen
Abstract : The Front Cover shows that acoustic emission is a promising technique that allows degradation of battery materials such as particle fracture to be probed in a non‐destructive manner. More information can be found in the Article by T. Brezesinski, J. Janek and co‐workers .